2 Compiled Laws of the State of Utah 1632 (1919) - (:unkn) unknown (My University, 1905)
§ 8494: "Any person who sells, gives, or disposes of, or offers to sell, give or dispose of any pistol, gun, target gun, or other firearm to any person under the age of fourteen years is guilty of a misdemeanor."
Keywords: TRANSFER - MINORS